Prolonged Systemic Inflammatory Response Syndrome Predicts Atrial Fibrillation after Cardiac Surgery - Viikinkoski, Emma; Lehto, Joonas; Relander, Arto; Jalkanen, Juho; Gunn, Jarmo; Vasankari, Tuija; Biancari, Fausto; Airaksinen, KE Juhani; Hollmén, Maija; Kiviniemi, Tuomas O (United Kingdom, 2026)
Objectives: Cardiac surgery and the use of cardiopulmonary bypass (CPB) lead to short-lasting postoperative inflammatory response and some patients fail to adapt to the stress leading to a prolonged systemic inflammatory response (SIRS). We aimed to identify the risk factors for prolonged SIRS and whether this may affect the onset of short- and long-term postoperative atrial fibrillation (AF) after adult cardiac surgery patients.
Methods: The CAREBANK biobank study consists of prospectively enrolled patients undergoing adult cardiac surgery from 2016 to 2021 with on-going follow-up data. This substudy included patients operated on with or without the use of CPB.
Results: Overall, 982 patients underwent cardiac surgery, 824 (84%) patients using CPB. Prolonged SIRS was observed in 62 (6.3%) patients. Transfusion of packed red blood cells (OR 1.9, 95%, CI 1.1-3.5, p = 0.03), and the first postoperative day C-reactive protein level (OR 1.2, 95%, CI 1.0-1.3, per 10 units, p = 0.002) were associated with the development of prolonged SIRS in a multivariable analysis. Patients with prolonged SIRS had more adverse events during index hospitalization, mainly driven by the higher incidence of postoperative AF compared to non-SIRS patients (OR 2.4, 95%, CI, 1.4-4.0, p < 0.001). At two-year, the incidence of post-discharge AF was higher compared with non-SIRS patients (HR 2.0, 95% CI, 1.1-3.6, p = 0.024).
Conclusions: A subset of cardiac surgery patients demonstrates impaired adaptation to the perioperative inflammatory response, placing them at increased risk for atrial fibrillation both early after surgery and following discharge.